Penerapan Internet of Things (IoT) Pada Sistem Pengaman Pintu Menggunakan Modul Nodemcu ESP8266 Berbasis Telegram - Endah Yaodah Kodratilah; Nur Sodik; U. Darmanto Soer (Jurnal SIGMA, 2022)
Technological developments are carried out to support human needs to be more practical in life, one of which is in the household sector. This is the basis of this research. By using NodeMCU and Arduino Uno as microcontrollers for Smart Home systems with the IoT concept. With the creation of a Smart Home system with the IoT concept, it is hoped that the value of efficiency and security can be achieved at home. In this research, NodeMCU is implemented as a microcontroller in Smart Home system with IOT concept. This system is designed by using Telegram Messenger and keypad as input or notification media on this system. When inputting chat, the chat input data is read by the program for verification. If the verification is not successful then the system does not respond followed by reprogramming the chat input, if the verification is successful then the BOT will respond then send an input signal to the microcontroller for processing, after processing the microcontroller will send an output signal (On/Off) to be sent to the relay which will be forwarded to the output components (Solenoid Door lock, magnetic sensor, Buzzer). By implementing a Smart Home system with the IoT concept, we can take advantage of existing technology. The Smart Home system with the IoT concept is also safe because only people who have certain access can control the house such as unlocking the door and turning on the magnetic sensor remotely. Keywords: NodeMCU ESP8266, Arduino Uno, magnetic sensor, door solenoid, relay, power supply, buzzer, telegram and arduinoIDE